Unpacking early memories: Pre-school teacher candidates’ attitudes towards special needs - Vezne, Rabia; Sardohan Yıldırım, Emel (Southeast Asia Early Childhood Journal, 2022)
The Individuals’ experiences and memories about people with special needs affect their attitudes, behaviours and perceptions towards these individuals in the following years. This study aims to discover pre-school teacher candidates’ early memories about people with special needs and understand the effect of these early memories on teacher candidates’ attitudes towards people with special needs. The convergent parallel design of mixed-method research is used in this study. The researchers used extreme or deviant case sampling of purposeful sampling. 110 teacher candidates at pre-school teaching department of Akdeniz University answered the survey and open-response questions. The survey included the Multidimensional Attitudes Scale toward Persons with Disabilities (MAS) scale developed by Findler et al. (2007) and adopted into Turkish by Yelpaze and Türküm (2018). The quantitative data were imported into the SPSS program to calculate descriptive and inferential statistics. To analyse the attitudes of teacher candidates, mean and standard deviation were conducted. For the qualitative analysis, 10 teacher candidates in the highest and in the lowest (5 participants from each group) on Turkish version of MAS were selected. The data were coded by using NVIVO 10. According to the analysis of qualitative data, pre-school teacher candidates’ memories included positive and negative aspects together; like sadness, fear, astonishment, and helplessness. On the other hand, according to the analysis of quantitative data, teacher candidates’ attitude towards people with special needs were mostly close to negative in affection and behaviour. Therefore, it can be thought that the memories of teacher candidates towards individuals with special needs do not affect their attitudes.